The role of social media and confirmation bias in victimization: Information consumption and opinion polarization - Talukder, Md Ishtiaq Ahmed; Rahaman, Mahabubur (International Journal of Emerging Trends in Social Sciences, 2023)
Technological advancement has contributed to the smooth and fast communication system where social media remain the top priority for human kind. Confirmation bias is a cognitive bias of human tendency to deducting information. Therefore, getting biased through unconfirmed media stories became a disease to the modern society. This article aims to explore and analyse the phenomenon of confirmation bias in cyber media, focusing on its impact on information consumption and polarization of opinions within online environments. Drawing upon existing literature and theoretical frameworks, namely Social Identity Theory, Cognitive Dissonance Theory, Selective Exposure Theory, and Agenda Setting Theory, this study provides a comprehensive understanding of the underlying mechanisms and effects of confirmation bias in the digital age. The research design combines qualitative analysis of selected scholarly articles and quantitative analysis of user data from social media platforms. The analysis provides a comprehensive understanding of the impact of confirmation biases in cyber media by synthesizing insights from scholarly literature and analysing user data. It helps identify the mechanisms through which confirmation biases manifest in online environments, sheds light on the potential consequences of such biases, and informs strategies for addressing and mitigating their effects.